Hispidulin Enhances Temozolomide (TMZ)-Induced Cytotoxicity against Malignant Glioma Cells In Vitro by Inhibiting Autophagy. (28th June 2022) - Chen, Zhihua; Zhu, Guofeng; Sheng, Chunpeng; Lei, Jianwei; Song, Sihui; Zhu, Jianming
Abstract : Temozolomide (TMZ), an oral alkylating agent, is the widely used first-line chemotherapeutic reagent for glioma in clinical practice. However, TMZ-induced autophagy is another cellular process favoring glioma cell survival. This study aimed to explore whether hispidulin can facilitate TMZ-induced cell death of glioma. The MTT assay showed that coadministration with hispidulin and TMZ could significantly decrease the viability of glioma U87MG cells. Meanwhile, hispidulin administration was also observed to promote TMZ-induced apoptosis. Furthermore, additional hispidulin treatment further elevated TMZ-induced expression of Bax, cleaved-caspase-9, and cleaved-caspase-3 protein but decreased Bcl-2 protein expression in U87MG cells. We also observed that hispidulin suppressed TMZ-induced autophagy to promote apoptosis, as showed by decreased AVOs and LC3B-I/II protein expression. These results collectively suggested that the combination of hispidulin and TMZ could improve the antitumor efficiency of TMZ against malignant gliomas.